The Association of Myasthenia Gravis with HLA class II Antigens in Iraqi Patients (Baghdad Science Journal, 2013)
The nature and intensity of the association of myasthenia gravis (MG) with distinct human leukocyte antigen (HLA) haplotypes differ between ethnic populations, so this study determined the association of HLA class II antigens with myasthenia gravis (MG) in Iraq.The study included Iraqi patients diagnosed with MG and two control groups the first of 54 insulin dependent diabetes mellitus patients and the second of 237 subjects as a normal control group. The test used was microlymphocytotoxicity test.The work was done in the Teaching Laboratories/Medical City/Baghdad.Results: positive associations were observed (etiological risk factors) as follows:1. HLA-DR locus showed one positively associated allele when compared to healthy control and this was HLA-DR3 (RR: 21.05, EF0.73, & P value ? 0.05), While when compared to IDDM control no significant association appeared (since the same allele is positively associated with IDDM). 2. HLA-DQ locus showed only one positively associated allele when compared to healthy control; this was HLA-DQ2 (RR 4.67, EF 0.50, and P value ? 0.05). While no significant association appeared when compared to IDDM control. Other important clinical association were observed; association with age, gender, strong stressful events, thymoma, and other autoimmune disorders.Conclusion: The positively associated antigens which were found as follows HLA-DR3 and HLA-DQ2, while no negative association was detected.